2014
DOI: 10.1890/13-0430.1
|View full text |Cite
|
Sign up to set email alerts
|

Priming in the microbial landscape: periphytic algal stimulation of litter‐associated microbial decomposers

Abstract: Microbial communities associated with submerged detritus in aquatic ecosystems often comprise a diverse mixture of autotrophic and heterotrophic microbes, including algae, bacteria, protozoa, and fungi. Recent studies have documented increased rates of plant litter mass loss when periphytic algae are present. We conducted laboratory and field experiments to assess potential metabolic interactions between natural autotrophic and heterotrophic microbial communities inhabiting submerged decaying plant litter of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
129
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 69 publications
10
129
4
Order By: Relevance
“…Algae and heterotrophic bacteria grow in close association (Battin et al 2007), and similar responses to nutrients and warming may not have been independent but instead linked to an exchange of resources within the biofilm (Kuehn et al 2014). In a concurrent study, we demonstrated that nutrient enrichment alone had no effect on bacterial growth without the simultaneous addition of a carbon source (K.H.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algae and heterotrophic bacteria grow in close association (Battin et al 2007), and similar responses to nutrients and warming may not have been independent but instead linked to an exchange of resources within the biofilm (Kuehn et al 2014). In a concurrent study, we demonstrated that nutrient enrichment alone had no effect on bacterial growth without the simultaneous addition of a carbon source (K.H.…”
Section: Discussionmentioning
confidence: 99%
“…Although algae are not likely to contribute substantially to the structural formation of peat (given their labile nature), they may influence the metabolic environment for heterotrophic metabolism by regulating the fate of nutrients and organic matter at the peat surface (Wyatt et al 2012). Algae can do this in several ways, including through the release of exudates (Bertilsson and Jones 2003), which typically consist of simple carbohydrates and amino acids (Wyatt et al 2012) and promote heterotrophic metabolism in the surrounding biofilm (Kuehn et al 2014). Other important functions of algae in wetlands are dependent on species membership, including nitrogen (N) fixation, which is limited to a few groups of heterocyst-forming cyanobacteria (i.e., blue-green algae).…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence for the priming effect in stream biofilms remains equivocal at present. There is suggestive evidence that the presence of algae stimulates bacterial and fungal growth that is associated with leaf litter 72,73 , but no evidence for the priming effect could be found in hyporheic biofilms 74 .…”
Section: Formation and Physical Structurementioning
confidence: 99%
“…However, evidence for the priming effect in stream biofilms remains equivocal at present. There is suggestive evidence that the presence of algae stimulates bacterial and fungal growth that is associated with leaf litter 72,73 , but no evidence for the priming effect could be found in hyporheic biofilms 74 .The extensive diversity of bacteria in stream biofilms makes it extremely difficult to establish relationships between bacterial diversity and biofilm function. For example, complementarity among algal species has been shown to increase the uptake of nitrate by stream biofilms 75 but, although it is plausible that this may also occur among bacteria in biofilms, we are not aware of any such study.…”
mentioning
confidence: 99%
“…The interaction of these different organic matter pools has potentially important implications for carbon cycling in stream ecosystems (9). For instance, labile organic matter may enhance microbial degradation of recalcitrant organic matter through priming or cometabolism (1,(9)(10)(11). Therefore, knowledge of the structure and functioning of the microbial communities dwelling in the hyporheic zone and their potential response to variations in the DOM supply is important to better assess the role of the hyporheic zone for biogeochemical processes.…”
mentioning
confidence: 99%